Respuesta :

-(x+2)=2(3x-6)

-x-2=6x-12

  +12     +12

-x+10=6x

+x       +x

10=7x

/7   /7

1 3/7=x

hope it helps!

if not, sorry...

Answer:

x = 1.43 or [tex]\frac{10}{7}[/tex]

Step-by-step explanation:

First use the distributive property to apply the negative to the left, and the 2 to the right side.

Now your problem looks like:

-x + 2 = 6x - 12

Next,  we can add 12 to both sides to get rid of the -12 on the right side.

Now, your problem looks like:

-x + 10 = 6x

Next, to get the coefficient on the right isolated, you can add x to both sides to get rid of the -x on the left.

Now, your problem looks like:

10 = 7x

Next, you can divide both times by the number in the coefficient term, which is 7.

Now, your problem is solved, and looks like:

x = 1.43 or x = [tex]\frac{10}{7}[/tex]

~theLocoCoco

ACCESS MORE